Therapeutic adventures with autistic children : connecting through movement, play and creativity - Torrance, Jonas (Jessica Kingsley Publishers, 2018)
Empowering readers to approach children with autism with greater flexibility and understanding, this collection of inspiring narratives shows the positive impact creative therapy has on characteristics of autism. The child-centred, multi-creative approach displays an exciting array of beneficial therapies such as dance, music and meditation.